SharePoint 2010 as a Development Platform - Krause, Jörg (Apress, 2013)
Contents at a Glance ....iv ■Contents ...v ■About the Authors .........xii ■About the Technical Reviewer .... xiv ■Acknowledgments........xv ■Introduction .. xvi Part 1: Basic Tasks......1 ■Chapter 1: Developer Basics .....3 ■Chapter 2: Architecture......51 ■Chapter 3: Accessing the API ....117 ■Chapter 4: Data Access ....165 ■Chapter 5: External Data Access 255 ■Chapter 6: Web Parts .....295 ■Chapter 7: Templates ....387 ■Chapter 8: Application Techniques ...429 ■Chapter 9: Solution Deployment....481 Part 2: User Interface ..553 ■Chapter 10: Extending the User Interface ...555 ■Chapter 11: Using Web Controls.623 ■Chapter 12: Client Programming....711 ■Chapter 13: Integrating Silverlight...783 ■Chapter 14: Integrating Charts and Maps ..827 Part 3: Advanced Techniques..881 ■Chapter 15: Forms Services and InfoPath....883 ■Chapter 16: Workflows.........947 ■Chapter 17: Administrative Tasks..1035 ■Chapter 18: Enterprise Features ..1057 ■Index ..1083